Penerapan Prinsip Mengenali Pengguna Jasa bagi Notaris menurut Undang-Undang Nomor 2 Tahun 2014 - Syafira, Rizki Putri; Purba, Hasim; Agustining, Agustining; Suprayitno, Suprayitno (Universitas Medan Area, 2024)
Notaries play a crucial role in making authentic deeds by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions (UUJN-P). This research uses normative legal research methods with a descriptive nature, collecting data through literature research and field studies. The results show that the application of the Principle of Recognizing Service Users (PMPJ) by Notaries has become important in notary practice, especially after the issuance of the Minister of Law and Human Rights Regulation Number 9 of 2017. Despite the dilemma between maintaining the confidentiality of client information and complying with PMPJ principles, steps have been taken to ensure compliance with applicable regulations, including reporting suspicious transactions to the Financial Transaction Reporting and Analysis Center (PPATK) if necessary. Thus, the application of PMPJ principles by Notaries is essential in maintaining integrity and compliance with applicable regulations in notary practice.